Oh, what a tangled web we weave - New Sunday Times (New Sunday Times, 2014)
Everyone lies at some point in their lives -whether to keep from hurting someone, avoid further argument, or other reasons. But what if you're finding that you're starting to lie online - when you are deliberately posting status updates or tweets to create stories of a life that is not entirely real?